“Le devoir des époux”: Michel Foucault’s Reading of John Chrysostom’s Marital Ethic in Histoire de la sexualité 4: Les aveux de la chair ([1982–1984] 2018) - De Wet, Chris L. (Religion & theology, 2020)
The purpose of this article is to examine and evaluate Michel Foucault’s use of John Chrysostom’s (c. 349-407 CE) views on marriage and sexuality, as it is expounded in Foucault’s fourth volume of Histoire de la sexualité, Les aveux de la chair (2018). The following question is asked: does Foucault have anything new and relevant to say to current scholarship of John Chrysostom, especially in terms of his views about sexuality and marriage? The article brings Foucault’s contribution into dialogue with more or less current scholarship of Chrysostom. The study first examines the sources Foucault used for Chrysostom, and then critically delineates and assesses Foucault’s argument regarding marriage in John Chrysostom. In the analysis of Foucault’s reading of Chrysostom’s marital ethic, attention is given to three central aspects present in the chapter, “Le devoir des époux” (“The Duty of the Spouses”). First, the links Foucault establishes between the micro-politics of sexuality (and the domus or private life) and the macro-politics of the Christian Empire is discussed. Second, it is asked how Foucault reconstructs Chrysostom’s marital ethic as a type of technē for the married life, including how Foucault attempts to deconstruct the dichotomy between marriage and virginity. Finally, the study analyses how Foucault interprets Chrysostom’s view of the conjugal relationship as one based on the rights of property ownership and debt.